Prolonged grief disorder: A bibliometric analysis. - Koukopoulos, Anastasios; Neimeyer, Robert A. (Death Studies, 2024)
Prolonged Grief Disorder (PGD) has become a subject of increased interest among both researchers and practitioners, owing both to its recent inclusion in the DSM-5-TR and the growing evidence of widespread complications of bereavement in the context of the COVID-19 pandemic. From a set of 467 studies obtained from the Scopus database during the period 2009 to 2022, the present research provides bibliographic data on the most influential authors on the subject, most relevant journals based on the number of documents published, a keyword analysis of the focus of this work, and an overall characterization of the scientific literature on PGD. The Biblioshiny application along with VOSviewer software was used for the analysis and visual depiction of the results. Both the scientific and applied implications of this analysis are discussed.